A novel comprehensive CFD-based model for municipal solid waste incinerators based on the porous medium approach. (15th October 2022) - Hoang, Quynh N.; Van Caneghem, Jo; Croymans, Tom; Pittoors, Rudi; Vanierschot, Maarten
Highlights: A 2D CFD-based model for municipal solid waste incineration in grate-firing systems. MSW characterization in terms of cellulose, hemicellulose, lignin, and polyethylene. Treatment of the particle movement using the mass movement approach. Two-way coupling between the waste bed and freeboard models. A fair agreement between the simulation results and industrial measurements. Abstract: Simulation of municipal solid waste (MSW) grate incinerators is important to enhance the energy and material recovery potential of waste to energy plants. A grate incinerator consists of the waste bed on a grate and the freeboard. While the gas combustion in the freeboard can be readily solved by available CFD codes, modeling the waste combustion has been a challenge. In this paper, a comprehensive 2D CFD-based model has been developed to simulate on-grate MSW incineration. The waste bed is modeled as a porous zone with local volume-averaged properties. The gas flow is obtained using a commercial CFD code, while the solid phase is solved using an in-house code written in C. A new approach to characterize MSW is proposed to reduce the heterogeneity of waste while being capable of addressing its thermochemical characteristics. The model includes the effects of the bed packing on the gas flow. It also employs the mass movement approach and the walking column approach to account for the particle movement on the moving grate. A 33 MW waste incinerator under two operating conditions has been modeled, including an iterative coupling between the waste bed and the freeboard. The simulation results are compared with industrial measurements in the freeboard, and a discussion about the numerical and measurement uncertainty is provided. Given the complexity of the system, the agreement between numerical and measured results is fair. By means of the model, the trend of bed height, temperature, composition and decomposition rates along the grate were analyzed. It is shown that the primary air flows and grate speeds can be effectively controlled to ensure smooth operation of waste incinerators with varying waste compositions.